Bionical attitude carp hyperplasia spawning ground - Yang Chengsheng (2016)
The utility model discloses a bionical attitude carp hyperplasia spawning ground, characterized by, the laying nest comprises net piece adherance, reed mat, sinker, uses the utility model discloses the spawning ground at carp reproductive season, sets up the active region of carp activity to the reed mat, and net piece adherance forms the sheltered situation, and induced carp moves about, perches between the net piece adherance in spawning ground, treats the male and female carp back of estrusing, can lay eggs in the spawning ground, and on the roe attached to net piece adherance, partial ovum grain sank on the reed mat, adheres and hatches on the reed mat, the utility model relates to a simply, convenient to use, low cost, easily preparation, it is effectual to attach the ovum, has spreading value. 本实用新型公开了种仿生态鲤鱼增殖产卵场，其特征是，产卵巢由网片附着基、苇席、沉子组成，使用本实用新型产卵场，在鲤鱼繁殖季节，把苇席设置鲤鱼活动活跃的区域，网片附着基形成隐蔽场所，诱导鲤鱼在产卵场的网片附着基间游动、栖息，待雌雄鲤鱼发情后，即可在产卵场产卵，鱼卵附着于网片附着基上，部分卵粒沉于苇席上，黏着在苇席上孵化；本实用新型设计简单、使用方便、成本低廉、易于制作，附卵效果好，有推广价值。